2017
DOI: 10.1007/s11121-017-0840-y
|View full text |Cite
|
Sign up to set email alerts
|

A Pre-Post Evaluation of OpenMinds: a Sustainable, Peer-Led Mental Health Literacy Programme in Universities and Secondary Schools

Abstract: Engaging young people in the design and delivery of mental health education could lead to more effective interventions; however, few of these interventions have been evaluated. This study aimed to gain preliminary evidence with regards to the efficacy and acceptability of OpenMinds: a peer-designed and facilitated mental health literacy programme for university and secondary school students. The programme involves a structured programme of education and training for university medical students, who then delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 38 publications
1
31
0
2
Order By: Relevance
“…Previous research provides evidence that specifically identifies peers as a critical conduit for reducing stigma, increasing mental health literacy, generating health promoting communities, and promoting help‐seeking behaviour 23 . In considering the high rates of mental health issues in university students, 2 the potential negative outcomes of untreated mental health issues on academic achievement and undesirable life trajectories, 10 the reported patterns of limited help that university students seek, 1,6,7,24 and the role of peers in increasing mental health literacy, 25,26 this study corroborates previous research that has found peer‐to‐peer event delivery as an effective strategy to promote healthy behaviours among university students 22,27 . In the present study, activities that were directly delivered by student peers were reported to be the ones that most supported student well‐being.…”
Section: Discussionsupporting
confidence: 82%
“…Previous research provides evidence that specifically identifies peers as a critical conduit for reducing stigma, increasing mental health literacy, generating health promoting communities, and promoting help‐seeking behaviour 23 . In considering the high rates of mental health issues in university students, 2 the potential negative outcomes of untreated mental health issues on academic achievement and undesirable life trajectories, 10 the reported patterns of limited help that university students seek, 1,6,7,24 and the role of peers in increasing mental health literacy, 25,26 this study corroborates previous research that has found peer‐to‐peer event delivery as an effective strategy to promote healthy behaviours among university students 22,27 . In the present study, activities that were directly delivered by student peers were reported to be the ones that most supported student well‐being.…”
Section: Discussionsupporting
confidence: 82%
“…Orkibi 2014 [35]The effect of drama-based group therapy on aspects of mental illness stigmaIsraelMI5 PW MI, 7 communityDrama (therapy); 20 weekly, 2-h sessionsIntrapersonalCommunityMulti-Country Validated MI Stigma scales at each of 14 session2Significant;CI not given;ES not given17. Patalay, Annis, Sharpe, Newman, Main, Ragunathan, Parkes, Clarke 2017 [17]A Pre-Post Evaluation of OpenMinds: a Sustainable, Peer-Led Mental Health Literacy Programme in Universities and Secondary SchoolsUKMI234 community, 40 HCWEducation; 2 workshops over 3 weeksInterpersonalCommunitySocial Distance Measure used in the UK at pre-and post-interventionSignificant;CI not given;ES odds ratio: 0.8518. Pinfold, Thornicroft, Huxley, Farmer 2005 [36]Active ingredients in anti-stigma programs in mental healthUKMIPW MI, community (109 police, 78 adults, 472 school students)Education, social marketing, contact; 2, 2-h sessions; 2, 50-min school sessions;IntrapersonalInterpersonalCommunityMulti-Country Validated social distance scales at pre- and post-interventionSignificant;CI not given;ES not given19.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the 24 studies examined one stigma reduction strategy across more than one level. For example, Patalay and colleagues [17] trained university medical students in the UK to lead workshops with secondary school students on mental health conditions and services (educational strategy). Investigators measured medical students’ levels of stigma and impact on the interpersonal level to examine the workshop leadership’s potential impact on medical students’ future practice behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests being a peer educator (the individual delivering education to their peers) may increase self-esteem and improve social skills (Webel et al, 2010). However, there is limited research on peer-led initiatives around mental health in schools (Patalay et al, 2017). This evaluation was designed to test the effectiveness of peer education for universal, preventative mental health information through the Peer Education Project (PEP).…”
mentioning
confidence: 99%